(untitled) (American Journal of Islam and Society, 2013)
This book will be of interest to scholars in a variety of fields and disciplines: Islamic studies (history, thought, institutions, and modern developments), history, religion, anthropology, and sociology, to name a few that immediately come to mind. The book’s great virtue lies in its bringing together two heretofore somewhat antagonistic or apparently mutually exclusive scholarly temperaments to focus on a problem (or rather a cluster of problems) of the very first importance, articulated as the title of a seminal article by one of the great minds of the last century engaged in the academic pursuit of Islamic history: How did the early Shi‘a become sectarian? Marshal Hodgson’s interest and task in that complex and erudite study (published in 1955) has been admirably continued and, in a real sense, consummated in this excellent book. One of the many reasons the question as well as the answers it may generate are so important (even urgent, one might add) is because to ask how the early Shi‘a became sectarian is also to ask how Sunni Islam eventually came to be configured in its classical and enduring form, how Sufism arose, and how Islam acquired its singular cosmopolitan profile frequently characterized by the perhaps spurious prophetic hadith: ikhtilOEf ummati raúmah (Disagreement in my community is a divine mercy) ...